Determining Factors for Students' Decision to Choose Private Islamic Religious Universities: The Role of Word of Mouth and Brand Image - Siswanto, Iwan; Silahudin, Agus; Siregar, Kardina Engelina; Eriani, Eva (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to analyze the influence of word of mouth and brand image on students' decisions in choosing a university at the Imam Syafii Islamic Religious Institute (IMSYA) Indonesia. This study uses a quantitative approach with a type of causal associative research. The population in this study is all students in the first semester of the 2025/2026 batch which totals 456 students, with a sample of 213 respondents determined using the Slovin formula. The data collection technique was carried out through a questionnaire with a Likert scale, which has been tested for validity and reliability. Data analysis used prerequisite tests, F tests, and determination coefficients with the help of SPSS. The results of the study show that word of mouth and brand image partially or simultaneously have a significant effect on students' decisions in choosing higher education. Brand image has a more dominant influence than word of mouth. Overall, both variables make a considerable contribution in explaining student decisions. These findings show that positive social communication and a strong institutional image, especially based on religious values, are important factors in increasing student interest, even in relatively newly developed universities.